Loading Rate Dependence of Rock Strength Under Triaxial Compression - Tang, Yang; Zhang, Hailong; Xu, Jiang; Okubo, Seisuke; Liu, Xinrong (Frontiers in Earth Science, 2021)
Knowledge regarding the time-dependent behavior of rocks is essential to estimate the long-term deformation and stability of underground structures. The rock strength increases with the increasing loading rate. However, the loading rate dependence in post-failure regions under confining pressure remains unclear. In this study, triaxial compression tests were conducted on four types of rocks to examine the loading rate dependence in both peak and post-failure regions. Results demonstrate that an increase in residual strength with a tenfold increase in the strain rate was approximately proportional to 4% of the residual strength. Furthermore, the increase in peak strength with a tenfold increase in the strain rate increased at a rate of approximately 4% of peak strength. The obtained results were applicable to all the sample rocks and can be easily employed for improving the constitutive equations. Finally, the effect mechanism of the confining pressure on the loading rate dependence of rock strength is discussed.